Discrimination between Fresh and Frozen-Thawed Fish Involved in Food Safety and Fraud Protection - Luca Maria Chiesa; Radmila Pavlovic; Maria Nobile; Federica Di Cesare; Renato Malandra; Davide Pessina; Sara Panseri (Foods, 2020)
This study aims to discriminate fresh fish from frozen/thawed by identification of the key metabolites that are altered during the freezing/thawing processing. Atlantic salmon (Salmo salar) and bullet tuna (Auxis rochei) were selected as they are representative of broad consumption, and susceptible to pathogen contamination. Atlantic salmon samples were subjected to the following regimes: −20 °C (24h) and −35 °C (15 h) freezing, then thawed respectively in the blast chiller and in the cold room and analyzed immediately or after 10 days; (2) bullet tuna samples were frozen at −18 °C and thawed after 15, 30 and 90 days. High resolution mass spectrometry based on untargeted metabolomic analyses and statistical data treatment confirmed significant variations in the quantity of certain metabolites: the amount of l-phenylalanine in salmon increased immediately after thawing while that of anserine decreased. The concentration of l-arginine and its metabolites was altered at the 10th day after thawing rendering them promising markers of salmon freezing/thawing. As regards bullet tuna, compounds resulting from lipid degradation (l-α-Glyceryl-phosphoryl-choline and N-methyl-ethanolamine phosphate) increased notably during the storage period. This approach could be used to reveal common fraudulent incidents such as deliberate replacement of fresh fish with frozen/thawed, with food safety risks as the primary implication.